MEMULIHKAN KEUTUHAN CIPTAAN: Reï¬eksi Teologis Ekologi dalam Dimensi Pembebasan1 - Lake, Sani (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2016)
Building a whole human being is a dream that is placed in the principle of fair and peaceful. The Justice touches all human life equally. If it balanced, then the creation integrity will be created. Human is not only limited in quantitative pursued, but the quality of life is guided by good and right moral quality. Any person from any background, there was a call to oblige him to maintain, to preserve and to protect the integrity of creation.